Bis(isobutyl-ammonium) phthalate monohydrate - Ariffin, Azhar; Ng, S.W.; Norzalida, Z. (International Union of Crystallography, 2008)
N-Isobutyl-phthalimic acid hydrolyzes to the title salt, 2C4H12N +·C8H4O4 -·H2O, which adopts a hydrogen-bonded layer structure. In the anion, the carboxyl-ate groups are twisted with respect to the benzene ring [dihedral angles = 43.8 (1) and 50.9 (1)°].